New schizothoracine from Oligocene of Qaidam Basin, northern Tibetan Plateau, China, and its significance. Issue 2 (4th March 2018) - Yang, Tao; Zhang, Li; Li, Wenjia; Jia, Jingwei; Han, Lei; Zhang, Yuxin; Chen, Yingquan; Yan, Defei
ABSTRACT: The schizothoracines (Cyprinidae) are a type of endemic freshwater fish in and around the Tibetan Plateau. They are the only taxa among the cyprinids capable of tolerating the harsh environments of the plateau. The origin and evolution of schizothoracines are thought to be closely linked to the rise of the Tibetan Plateau; however, complete fossil schizothoracines are rare. Herein, we report a new Oligocene genus and species of the subfamily Schizothoracinae, Paleoschizothorax qaidamensis, gen. et sp. nov., from the Qaidam Basin, northeastern Tibetan Plateau, China. This is the earliest credible fossil schizothoracine by far, and the discovery demonstrates that schizothoracines originated no later than the Oligocene. We deduce that the origin of schizothoracines is closely related to the global climate shift at the Eocene–Oligocene transition. Our findings contribute to efforts to comprehend the influence of the global climatic shift on Asian environments from a biotic perspective. Additionally, the fossils reflect a warm, low-altitude environment before the uplift of the Tibetan Plateau. The fossil fish records indicate that vast drainages existed in the northern Qaidam Basin during the Oligocene and that the basin has experienced significant regional uplift since the Neogene, leading to the extinction and migration of fishes. http://www.zoobank.org/urn:lsid:zoobank.org:pub:1E9D9016-5DF7-4A15-8F10-C713FD428DCA Citation for this article: Yang, T., L. Zhang, W. Li, J. Jia, L. Han, Y. Zhang, Y. Chen, and D. Yan. 2018. New schizothoracine from Oligocene of Qaidam Basin, northern Tibetan Plateau, China, and its significance. Journal of Vertebrate Paleontology. DOI: 10.1080/02724634.2018.1442840.